2021
DOI: 10.1177/17562848211023399
|View full text |Cite
|
Sign up to set email alerts
|

The elderly IBD patient in the modern era: changing paradigms in risk stratification and therapeutic management

Abstract: The incidence and prevalence of inflammatory bowel disease (IBD) is rising in the elderly population. Compared with patients with onset during their younger years, patients with elderly onset IBD have a distinct clinical presentation, disease phenotype, and natural history. Genetics contribute less to pathogenesis of disease, whereas biological changes associated with aging including immunosenescence, dysbiosis, and frailty have a greater impact on disease outcomes. With the advent of an increasingly wider arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 119 publications
0
10
0
4
Order By: Relevance
“…There was no difference for symptoms that lead to a diagnosis of IBD, except for abdominal pain, which was more common amongst adults, both for UC and CD, respectively. This unreported abdominal pain in the elderly might be due to decreased intestinal motility or better ability to tolerate pain 21,17 .…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference for symptoms that lead to a diagnosis of IBD, except for abdominal pain, which was more common amongst adults, both for UC and CD, respectively. This unreported abdominal pain in the elderly might be due to decreased intestinal motility or better ability to tolerate pain 21,17 .…”
Section: Discussionmentioning
confidence: 99%
“…IBD diagnosed or occurring at an older age differs from adult-onset IBD, with a distinct phenotype and disease manifestation. 59 UC was found to be more common than CD in elderly IBD patients. For example, a French study showed that left-sided UC was more common in elderly patients, 60 whereas a South Korean study found that rectitis was more common.…”
Section: Previous Researchmentioning
confidence: 92%
“…1 Furthermore, diagnosis can be difficult due to atypical symptoms that can resemble other agerelated conditions. 2 The European Crohn's and Colitis Organisation has defined elderly onset IBD as that diagnosed at 60 years or older. 3 However, the definition is not consensual, with studies using cutoffs up to 75 years old.…”
Section: N V I T E D E D I T O R I a L Editorial: Elderly Onset Infla...mentioning
confidence: 99%
“…Given the current evidence, 2,7,8 it seems pertinent to include an A4 category, for patients with disease onset after 60, in the Montreal classification, and to enrol these individuals in observational studies and randomised controlled trials. The evaluation of the efficacy and safety of biologics in this population is particularly important, considering immunosenescence and pharmacokinetic peculiarities.…”
Section: N V I T E D E D I T O R I a L Editorial: Elderly Onset Infla...mentioning
confidence: 99%
See 1 more Smart Citation